Peningkatan Penguasaan Kosakata Bahasa Inggris Siswa Melalui Pembelajaran Bahasa Berbantuan Komputer - Syamsiarna Nappu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2014)
This study aims at improving students’ mastery on English vocabulary using computer and nding out the effectiveness, ef ciency and the attractiveness of Computer- Assisted Language Learning (CALL) in English learning. It was carried out at State Junior High School 24 Makassar by using proactive action research method and intervention action model used by John Elliot. The data were collected and analyzed by using mixed method approach. Instruments used for collecting data in this study are questionnaires, documents, observation check list, interview, and achievement tests. The results showed that the students’ English vocabulary can be increased through the use of computer in Eng- lish language learning. Besides, it is also effective, ef cient and attractive to be used in English learning process.